A Review of Infections After Hematopoietic Cell Transplantation Requiring PICU Care: Transplant Timeline Is Key - Ferdjallah, Asmaa; Young, Jo-Anne H.; MacMillan, Margaret L. (Frontiers in Pediatrics, 2021)
Despite major advances in antimicrobial prophylaxis and therapy, opportunistic infections remain a major cause of morbidity and mortality after pediatric hematopoietic cell transplant (HCT). Risk factors associated with the development of opportunistic infections include the patient's underlying disease, previous infection history, co-morbidities, source of the donor graft, preparative therapy prior to the graft infusion, immunosuppressive agents, early and late toxicities after transplant, and graft-vs.-host disease (GVHD). Additionally, the risk for and type of infection changes throughout the HCT course and is greatly influenced by the degree and duration of immunosuppression of the HCT recipient. Hematopoietic cell transplant recipients are at high risk for rapid clinical decompensation from infections. The pediatric intensivist must remain abreast of the status of the timeline from HCT to understand the risk for different infections. This review will serve to highlight the infection risks over the year-long course of the HCT process and to provide key clinical considerations for the pediatric intensivist by presenting a series of hypothetical HCT cases.